DRUG-INDUCED IMMUNE THROMBOCYTOPENIA: PATHOGENESIS, DIAGNOSIS AND MANAGEMENT - Aster, Richard H (2009)
Drug-induced immune thrombocytopenia (DITP) can be triggered by a wide range of medications. Although many cases of DITP are mild, some are characterized by life-threatening bleeding symptoms. The pathogenesis of DITP is complex in that at least six different mechanisms have been proposed by which drug-induced antibodies can promote platelet destruction. It is possible in many cases to identify antibodies that react with platelets in the presence of the sensitizing drug, but the required testing is technically demanding and not widely available. Therefore, a decision on whether to discontinue an implicated medication in a patient suspected of having DITP must be made on clinical grounds. An algorithms is available that can be helpful in assessing the likelihood that a particular drug caused thrombocytopenia, but the most important single determinant in managing a patient is a high index of suspicion and a careful history of drug exposure in an individual who presents with acute, often severe thrombocytopenia of unknown etiology. How drugs induce platelet-reactive antibodies and how, once formed, the antibodies cause platelet destruction following exposure to the drug is poorly understood. Further studies to address these issues and characterize more completely the range of drugs and drug metabolites that can cause DITP are needed.